Membangun Generasi Cerdas dan Gemar Membaca: Implementasi Pojok Baca di Sekolah Dasar - Syaharuddin, Syaharuddin; Nurhakim, Syanabiawan Maryati; istiqamah, Nurul; Hidayat, M. Restu; Rianti, Riski Anwar; Widianti, Suciana; Nurlaelah, Nurlaelah; Hikmah, Nurul (Politeknik Penerbangan Indonesia Curug, 2025)
The reading interest of elementary school students in Indonesia is still relatively low, partly due to poorly managed and unattractive libraries. This condition is also evident at SDN 2 Sekotong Barat, where the school library is neglected, the book collection is disorganized, and reading room facilities are limited, so students rarely use it as a source of learning or entertainment. To address this problem, this Community Service (PKM) activity was carried out with the aim of increasing students' interest in reading through library revitalization. The methods used included reorganizing the book collection, painting the walls, providing tables, chairs, and reading carpets, and creating a child-friendly reading corner. The partners in this activity were 15 students from SDN 2 Sekotong Barat as the main beneficiaries. The evaluation was conducted through observation of student activities in the library, including the frequency of visits, reading time, and interaction with the new facilities. The results showed a 90% success rate, marked by an increase in student enthusiasm for reading for 20-30 minutes per visit.